Stable Radio Frequency Transfer Over Free Space by Passive Phase Correction - Yaqing Chen; Mingyu Jiang; Nan Cheng; Rui Wu; Jialiang Wang; Yanguang Sun; Fei Yang; Fufei Pang; Youzhen Gui; Haiwen Cai (IEEE Photonics Journal, 2019)
The frequency transmission over free-space link can effectively overcome the dependence of existing optical fiber time-frequency transmission technology on optical fiber network. In this paper, we demonstrate a passive phase correction technique over a 124 m long indoor atmospheric radio frequency (RF) dissemination. This scheme simplifies the system, and suppresses the effects of Rayleigh backscattering. We verify the feasibility of the scheme by transmitting 1 GHz RF signals over the atmospheric link. After timing fluctuation compensation, the relative frequency stability can reach 6.8 × 10−15 for 1 s and 3.2 × 10−17 for 103 s, the RMS timing fluctuation is 186 fs in 5000 s. It can be proved that the scheme is very effective in eliminating phase noise caused by atmospheric link.